DIVERSITY OF NEOGRASTOPODA IN LAMPUNG BAY - Hendrik A.W. Cappenberg (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
The research was conducted in April 2008 and March 2009, in the Lampung Bay on six locations: Lahu, Ringgung, Hurun Bay, Mutun, Pelabuhan Panjang, and Sebalang. The aims of this research were to determine the diversity of neogastropod and their condition in this bay. The neogastropod samples were collected by using square transect method. A total number of 176 individuals of neo-gastropod consisted of 15 species which were belong to 6 families were collected from the bay. Mo-rula Margariticola and Morula sp. (Muricidae) were the dominance species with relatively wide dis-tribution. The diversity index (H’) ranged between 0,90 – 2,10. The evenness index (e) ranged between 0.65 – 0.91, and the species dominant index (C) ranged between 0.15 – 0.49. The overall calculation indicated that the diversity of neogastropod in the Lampung Bay was relatively low. Comparison the diversiry of neogastropod from the other various areas in the coastal zone of Indonesia was also dis-cussed in this paper. Keywords: diversity, neogastropod, Lampung Bay.